2023
DOI: 10.1002/bit.28350
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the sulfate transporter‐encoding SULTR2 increases chromium accumulation in Chlamydomonas reinhardtii

Abstract: Hexavalent chromium [Cr(Ⅵ)] is a highly toxic contaminant in aquatic systems, and microalgae represent promising bioremediators of metal-containing wastewater.However, the metal-binding capacity of algal cells is limited. Therefore, we improved the cellular Cr(Ⅵ) biosorption capacity of Chlamydomonas reinhardtii by overexpressing the sulfate transporter gene SULTR2. SULTR2 was predominantly located in the cytoplasm of the cell, and few proteins mobilized to the cell membrane as a Cr transporter under Cr stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Previous research has reported that chromate, being analogous to sulfate, is actively transported across the cell membrane via sulfate permease in certain microorganisms. 41,42 However, the proteins responsible for chromate/sulfate uptake in filamentous fungi, including A. niger, have remained unidentified.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has reported that chromate, being analogous to sulfate, is actively transported across the cell membrane via sulfate permease in certain microorganisms. 41,42 However, the proteins responsible for chromate/sulfate uptake in filamentous fungi, including A. niger, have remained unidentified.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The mentioned studies provide compelling evidence that the activity of Cr­(VI) reductase is primarily localized in the cytoplasmic fraction of A. niger cells, indicating that Cr­(VI) in aqueous environments needs to be translocated into the cytoplasm before it can be reduced by cytoplasmic chromate reductase. Previous research has reported that chromate, being analogous to sulfate, is actively transported across the cell membrane via sulfate permease in certain microorganisms. , However, the proteins responsible for chromate/sulfate uptake in filamentous fungi, including A. niger , have remained unidentified.…”
Section: Resultsmentioning
confidence: 99%
“…reinhardtii has shown a significant capability for biosorption, effectively removing copper, boron, and manganese [64], arsenic [65], nickel [66], zinc, cadmium [67] and uranium [68]. In C. reinhardtii gene manipulation has been conducted to enhance the expression of the metal tolerance proteins metallothioneins [69], resulting in increased tolerance to cadmium [70], chromium [71], copper [72], mercury [73], and lead [74]. Biosorption in C. reinhardtii as a defense mechanism against silver nanoparticles involves an increase in phytochelatin and exopolysaccharides content, along with a decrease in glutathione levels [75].…”
Section: Chlamydomonas Phycoremediationmentioning
confidence: 99%